A focus on human capital in commercial and social entrepreneurship - Chauke, Matthews J. (My University, 2019)
Orientation: Critical reading on the aspects of human capital literature receives limited contributions to truly comprehend their effect on entrepreneurship activity, especially in a developing country, like South Africa. Although human capital theory is a key theme in entrepreneurship research, it has been acknowledged that the domain requires more attention to fully understand it. Research purpose: The purpose of this study is to establish the influence of human capital across various occupational preferences. Motivation for the study: Many from individual level to firm level in developing countries do not understand the effect of human capital aspects on entrepreneurship activity. Research design, approach and method: The empirical analysis of the study is cross-sectional, based on the data from the primary survey. Correlation and regression analysis was used for hypothesis testing. Main findings: The results indicated that human capital aspects have no significant relationship with entrepreneurial activity. Implication of the study: This empirical study extends the current knowledge on the effect of human capital aspects on entrepreneurship activities in a unique, culturally diverse country. like South Africa.
A research proposal submitted to the Faculty of Commerce, Law and Management, University of the Witwatersrand, in partial fulfilment of the requirements for the degree of Master of Management in Entrepreneurship and New Venture Creation, 2019
Keywords: Business enterprises; Social entrepreneurship; Social responsibility of business